PARTICLE SWARM OPTIMIZATION FOR SOLVING NLP AND MINLP IN CHEMICAL ENGINEERING - Jarboui, Bassem; Derbel, Houda; Eddaly, Mansour; Siarry, Patrick (Stochastic Global Optimization, 2010)
The following sections are included: Introduction The Initial Version of the PSO Algorithm Simple Modifications to the Original PSO Maximum velocity Inertia weight Constriction factor Stopping criteria Neighborhood Selection Strategies Global best / Local best PSO Extensions of Basic PSO Multi-Start PSO Algorithms Gravity Center Technique Application of PSO to Mixed-Integer Nonlinear Programming (MINLP) Applications to constrained problems Applications in chemical engineering Application of PSO to the NLP and MINLP Problems Initialization Handling discrete variables and bound checking Handling constraints Numerical Results Conclusion and Future Directions References